Ways of Developing the Media Literacy of the Future English Language Teacher in the Conditions of Modern War - Shykyrynska, Olha (Journal of Danubian Studies and Research, 2023)
The problem of counteracting media manipulation has become particularly acute in the conditions of modern war. The author considers media literacy as a key competence of the future teacher. Higher education should improve knowledge of how to counter hostile propaganda and disinformation, maintain emotional and psychological stability, avoid mass panic, and make correct decisions based on carefully verified information. The future English teacher must master the algorithm for checking the quality of the content of Ukrainian and foreign media; learn to research the expertise of authors, sources of information, in particular, Telegram channels; master digital tools for quick and effective photo and video authentication; familiarize yourself with the key narratives and tactics of Russian propaganda in order to successfully counter them; learn to identify manipulative media content, distinguish between disinformation and harmful propaganda narratives, in particular, to be able to independently create quality content.